ANALISIS DAYA TERIMA ANTENA AIRGRID M5HP CLIENT PT. JAWA POS NATIONAL NETWORK MEDIALINK PONTIANAK - ., Ya’ Zulhikma Akbar (Faculty of Engineering, Universitas Tanjungpura, 2016)
Antenna received power is one of the parameters that can indicate the quality of the Internet network used by the client. Technician PT. JPNN Media Link Pontianak installing client antenna to get good acceptance simply by estimating the distance and direction of the antenna manually into consideration to gain acceptance without performing mathematical calculations. This study was conducted on 10 client PT. JPNN Media Link Pontianak. Then the results of some research data comparisons will be drawn conclusions and suggestions about the factors that influence the quality of the received power antenna AirGrid M5HP client PT. JPNN Media Link Pontianak. The average yield received power at the antenna AirGrid M5HP 10 client PT. JPNN Media Link Pontianak is entered in both categories that have a range between -73 dBm to -66 dBm, based on the received power standards set by Ubiquiti Networks. From the testing that was done on 10 client, the client only 2 that have received power value in the category enough antenna, this is because the client 2 has the farthest distance of 20 km, the frequency used is also high at 5700 MHz and are a barrier in the beam path between the transmitter antenna and receiver antenna on the client 2. Factors that could cause the value of the received power decreases M5HP AirGrid antenna is the distance between the transmitter antenna and receiver antenna, the geographical situation of the earth through which the signal, frequency of use, and precision pointing of the antenna. Â Keywords: Receive Power Antenna, AirGrid M5HP, Media Link, Wireless. Â